S126 Description of palliative care support for copd patients within primary care in the uk. (15th November 2017) - Bloom, CI; Slaich, B; Smeeth, L; Stone, P; Quint, JK
Abstract : Introduction and Objective: Over 5% of UK deaths are secondary to COPD, only 1% less than from lung cancer. Yet, there remains a lack of palliative care support (PCS) for COPD patients, despite evidence that it improves their quality of life, improving both physical and physiological symptoms. NICE guidelines recommend its provision to all patients with end-stage COPD. Previous studies have found poor access for COPD patients in secondary care, this study aimed to assess PCS within primary care. Methods: Population-based open cohort study, January 2004 to June 2015, using electronic healthcare records (Clinical Practice Research Datalink). Associations with PCS were measured using logistic regression. Results: 92, 365 COPD patients were included (median follow-up=4.2 years). Only 7.5% received PCS; of whom 47% had lung cancer. Only 21% of all deceased COPD patients received PCS, and within 6 months from their death only 48% of those patients had received PCS, by 3 months before their death up to 69% had received PCS (figure 1 ). Around a third of these patients had co-existing lung cancer (figure 1 ). The adjusted odds of receiving PCS was 14.6 times higher for COPD patients with lung cancer than without (95% CI 13.2–16.1), and 6.3 times higher for deceased COPD patients with lung cancer than without (95% CI 5.6–7.1), adjusted for gender, age, BMI, MI, heart failure, stroke, smoking, GOLD stage, MRC Dyspnoea grade, exacerbations, anxiety and depression. The proportion of patients that received PCS yearly increased gradually from 2004 to 2014, but remained low, only 2.1% of patients in the cohort in 2014 received PCS in 2014. Conclusions: There was limited PCS for COPD patients; this appeared to be strongly driven by a co-existing diagnosis of lung cancer, not by their advanced COPD disease. PCS was often provided only towards the end of patient's lives; this may have been related to the difficulty in prognosticating the end-of-life for individuals with COPD. Encouragingly PCS increased yearly and could indicate recognition of its value and thus the requisite to discuss PCS with patients, however, this clearly remains an important unmet need.